Working Class Girls, Education and Post-Industrial Britain Aspirations and Reality in an Ex-Coalmining Community - Richards, Gill (Palgrave Studies in Gender and Education,, 2018)
This book explores the aspirations of 'working class' girls' in an ex-mining community in the UK. It highlights the difficulties present in these 'post-industrial' settings, which are often areas of severe deprivation, and questions whether these place limitations on the achievements of the girls within the community. Based on an eight-year longitudinal study of girls in three primary schools and two secondary schools which differed in levels of attainment, the book examines the girls' initial aspirations, decision-making, and later achievements when in post-compulsory education. It will be compelling reading for students, academics and practitioners in Education, offering a unique appreciation of how working-class girls balance their own aspirations with the educational opportunities perceived to be available to them.